Dialektika Konstitusionalisme dan Nilai Islam: Analisis Sistem Pengisian Jabatan Executif Di Indonesia - Supardi, Supardi; Khairani, Khairani (Nagari Law Review, 2025)
This articel examines the dialectical relationship between constitutionalism and Islamic values in the context of executive office appointment systems in Indonesia. Using normative juridical research methodology, this study analyzes how constitutional principles and Islamic values interact in shaping the mechanism of executive office appointments, particularly at national and regional levels. The findings indicate a harmonization between modern constitutional values and Islamic leadership principles, such as the concepts of shura, amanah, and justice. In-depth analysis reveals that Indonesia's executive office appointment system has adopted democratic elements that align with Islamic values, although not explicitly citing their religious sources. This research also identifies challenges in integrating these two value systems, especially in the context of legal pluralism and diversity of interpretations. In conclusion, a more comprehensive approach is needed to harmonize constitutional and Islamic values to strengthen the executive office appointment system in Indonesia.